PERAN GURU DALAM PELAKSANAAN BIMBINGAN REHABILITAS SOSIAL SISWA TUNARUNGU DI SLB NEGERI 1 SINJAI - K, Sulfikar.; Syam, St. Hajra; Darwis; mulkiyan (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2026)
This study aims to analyze the role of teachers in implementing social rehabilitation guidance for deaf students at SLB Negeri 1 Sinjai. The study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The research subjects were teachers directly involved in the learning and guidance of deaf students. The results of the study indicate that teachers have a very strategic role not only as teachers, but also as guides, facilitators, and supporters of students' social-emotional development. Rehabilitation guidance is carried out through the use of sign language, visual media, and an individual approach according to the students' needs. In addition, teachers also play a role in building communication with parents to support optimal student development. Despite various obstacles such as limited facilities, differences in student abilities, and a lack of professional staff, teachers continue to strive to overcome these through creativity and collaboration. The use of sign language has proven effective in improving communication, understanding, and self-confidence of deaf students in the learning process.